Perancangan Perancangan Sistem Informasi dalam Merekapitulasi Imunisasi Anak Menggunakan Microsoft Visual Studio dengan Metode Agile Development - Monika, Neng Anisa; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The problem of duplicate immunization data often occurs because existing systems do not have adequate validation. This causes child immunization data to be entered more than once, either due to errors in entering information or discrepancies in existing data in various programs or networks. In addition, the use of separate systems to recapitulate child immunization data also causes duplicate data. In order to overcome this problem, a system is needed that is able to detect duplicate immunization data. The Agile Development method aims to be used to design and develop this system repetitively and continuously. The Agile Development method allows developers to adapt to changes that occur during the development process and get feedback from users. In applying the Agile Development method, a user needs analysis is carried out involving medical experts, immunization officers, and user systems. Then a system design is carried out which includes validation of immunization data using predetermined rules. The system is also equipped with accurate reporting features and provides data duplication prevention. The result of applying this method is an information system that is able to detect duplication of immunization data so that immunization data reports become more accurate. Users can easily enter child immunization data information and the system will provide feedback if there is duplicate data. This increases the efficiency and accuracy of child immunization reports, and reduces errors and unwanted data duplication.